Plasma level and tissue expression of angiogenic factors in patients with hereditary hemorrhagic telangiectasia - Sadick, Haneen; Naim, Ramin; Sadick, Maliha; Hörmann, Karl; Riedel, Frank (International journal of molecular medicine, 2005)
The value of angiogenic factors interleukin-8 (IL-8) and vascular endothelial growth factor (VEGF) was determined in patients with hereditary hemorrhagic telangiectasia (HHT) to evaluate their role in HHT pathogenesis. IL-8 and VEGF were measured in plasma of 41 HHT patients and healthy controls by ELISA technique. In both groups, the IL-8 and VEGF tissue expression in cryostat sections of the nasal mucosa were then compared. VEGF plasma levels were significantly increased in HHT patients compared to healthy controls. In contrast, the IL-8 plasma levels in both groups did not show any significant difference. Compared to healthy controls, HHT tissue samples showed a weak IL-8 staining, whereas the VEGF staining was very strong. The plasma levels of VEGF and IL-8 could not be correlated to the patients' clinicopathological findings. Additionally to the angiogenic pro-inflammatory cytokine IL-8, the angiogenic factor VEGF seems to play a major role in HHT pathogenesis.